2012
DOI: 10.1017/jns.2012.10
|View full text |Cite
|
Sign up to set email alerts
|

Intake of polyphenol-rich pomegranate pure juice influences urinary glucocorticoids, blood pressure and homeostasis model assessment of insulin resistance in human volunteers

Abstract: Pomegranate juice (PJ; also known as pomegreat pure juice) provides a rich and varied source of polyphenolic compounds that may offer cardioprotective, anti-atherogenic and antihypertensive effects. The aim of this study was to investigate the effect of PJ consumption on glucocorticoids levels, blood pressure (BP) and insulin resistance in volunteers at high CVD risk. Subjects (twelve males and sixteen females) participated in a randomised, placebo-controlled cross-over study (BMI: 26·77 (sd 3·36) kg/m2; mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 56 publications
5
84
1
Order By: Relevance
“…After removing duplicates, 786 studies remained that were screened by reading both titles and abstracts, and from these, 734 articles did not meet the inclusion criteria. Eventually, of 52 potential relevant publications, a number of studies were excluded because of following reasons: 32 articles evaluated the effect of pomegranate consumption on other outcomes, 6 articles were not randomized controlled clinical trial (Al‐Dujaili, Stockton, Davidson, & Drummond, ; Heber et al, ; Lansky & Newman, ; Sahebkar, Gurban, Serban, Andrica, & Serban, ; Tsang et al, ; Turrini, Ferruzzi, & Fimognari, ), one study could not provide data on the pure effect of pomegranate or its products, and one study conducted on a blend of pomegranate juice and other juices without an appropriate control group (Díaz‐Rubio, Pérez‐Jiménez, Martínez‐Bartolomé, Álvarez, & Saura‐Calixto, ). Finally, 13 eligible RCTs were eligible to be included in the present systematic review and meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates, 786 studies remained that were screened by reading both titles and abstracts, and from these, 734 articles did not meet the inclusion criteria. Eventually, of 52 potential relevant publications, a number of studies were excluded because of following reasons: 32 articles evaluated the effect of pomegranate consumption on other outcomes, 6 articles were not randomized controlled clinical trial (Al‐Dujaili, Stockton, Davidson, & Drummond, ; Heber et al, ; Lansky & Newman, ; Sahebkar, Gurban, Serban, Andrica, & Serban, ; Tsang et al, ; Turrini, Ferruzzi, & Fimognari, ), one study could not provide data on the pure effect of pomegranate or its products, and one study conducted on a blend of pomegranate juice and other juices without an appropriate control group (Díaz‐Rubio, Pérez‐Jiménez, Martínez‐Bartolomé, Álvarez, & Saura‐Calixto, ). Finally, 13 eligible RCTs were eligible to be included in the present systematic review and meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Limited studies, however, have evaluated the effect of pomegranate consumption on weight in humans, with mixed results. Although some trials have shown that pomegranate has a weight reduction effect (González‐Ortiz, Martínez‐Abundis, Espinel‐Bermúdez, & Pérez‐Rubio, ), other studies found no significant effect (Ekhlasi, Shidfar, Agah, Merat, & Hosseini, ; Park et al, ; Sohrab et al, ; Tsang, Smail, Almoosawi, Davidson, & Al‐Dujaili, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of PJ studies in humans were randomized studies, placebo and double and triple blind 17,[21][22][23][24][25][26][27][28] ; as well as quasiexperimental studies. 29,30 One did not report the trial design in the article.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…The studies have evaluated the effect of PJ on parameters related to metabolic alterations in healthy, 17,24,28 obese, 23 and diabetic people, 21,26,27,29,30 with metabolic syndrome 25 and arterial pathologies, 27,31 and in women with polycystic ovarian syndrome. 22 In most studies, patients were excluded if they were taking any hypoglycemic drug, due to possible interaction with PJ compounds.…”
Section: Characteristics Of Participantsmentioning
confidence: 99%
“…Additionally, it has been shown that POM supplementation is an effective inhibitor of some cellular inflammation transcripts such as tumor necrosis factor α, nuclear factor -κB and cyclooxygenase-2 [14,15]. Similarly, POM supplementation has been shown to regulate expression of androgen-synthesizing genes in human prostate cancer cells [16] and to modulate hormonal profile by reducing cortisol [C] urinary output and fasting plasma insulin in volunteers at high CVD risk [17] and increasing testosterone [T] levels in testis torsion Wistar rats [18] and healthy humans [19].…”
Section: Introductionmentioning
confidence: 99%